Pengaruh Metode Permainan Ular Tangga Terhadap Hasil Belajar Peserta Didik Pada Pembelajaran Operasi Hitung Campuran Kelas IV SD Negeri 1 Lambheu Aceh Besar - Tasya, Tasya; Vitoria, Linda; Nurmasyitah, Nurmasyitah (Universitas Pahlawan Tuanku Tambusai, 2024)
The right learning method can influence the success of students. Teachers as educators need to know various teaching methods, especially in Mathematics lessons. The concept of learning and problem solving can be easily understood if the learning methods applied by students are appropriate. Game methods are often used in learning because they are considered effective. To determine the effectiveness of the snake and ladder game method on student learning outcomes in mixed arithmetic operations material. A quantitative approach was used in this research. The conclusion that can be drawn is that significant data processing results (2-tailed) were obtained at 0.000 < 0.05.